Chapter L'impossibile futuro dell'Europa o L'ultimo europeo 2284 di Miguel Real - Pais Simon, Maria Cristina (Libere carte, 2023)
In 2015, Miguel Real publishes O último europeu 2284 (The Last European 2284), where he conducts, through the tale of an ideal and utopian city, an analysis of a European Union crumbling around all sorts of conflicts. In the current context, does Europe have a future? Is the future of a community compatible with human nature? These are the questions we will be reflecting upon in this article, through the study of this work.